Antihyperglycemic effect of Orthosiphon stamineus Benth leaves extract and its bioassay-guided fractions - Mohamed, Elsnoussi Ali Hussin; Mohamed, Ali Jimale; Asmawi, Mohd Zaini; Sadikun, Amirin; Ebrika, Omar Saad; Yam, Mun Fei (MDPI, 2011)
Preliminary investigations were carried out to evaluate the antidiabetic effects of the leaves of O. stamineus extracted serially with solvents of increasing polarity (petroleum ether, chloroform, methanol and water); bioassay-guided purification of plant extracts using the subcutaneous glucose tolerance test (SbGTT) was also carried out. Only the chloroform extract, given at 1 g/kg body weight (b.w.), significantly reduced (P < 0.05) the blood glucose level of rats loaded subcutaneously with 150 mg/kg (b.w.) glucose. The active chloroform extract of O. stamineus was separated into five fractions using a dry flash column chromatography method. Out of the five fractions tested, only chloroform fraction 2 (Cƒ2), at the dose of 1 g/kg (b.w.) significantly inhibited (P < 0.05) blood glucose levels in SbGTT. Active Cƒ2 was split into two sub-fractions Cƒ2-A and Cƒ2-B, using a dry flash column chromatography method. The activities Cƒ2-A and Cƒ2-B were investigated using SbGTT, and the active sub-fraction was then further studied for anti-diabetic effects in a streptozotocin-induced diabetic rat model. The results clearly indicate that Cƒ2-B fraction exhibited a blood glucose lowering effect in fasted treated normal rats after glucose-loading of 150 mg/kg (b.w.). In the acute streptozotocin-induced diabetic rat model, Cƒ2-B did not exhibit a hypoglycemic effect on blood glucose levels up to 7 hours after treatment. Thus, it appears that Cƒ2-B functions similarly to metformin, which has no hypoglycemic effect but demonstrates an antihyperglycemic effect only in normogycemic models. The effect of Cƒ2-B may have no direct stimulatory effects on insulin secretion or on blood glucose levels in diabetic animal models. Verification of the active compound(s) within the active fraction (Cƒ2-B) indicated the presence of terpenoids and, flavonoids, including sinensitin.